Access to justice for sexual orientation and sex-gender identity based victims of discrimination and violence in Spain - Martín Aragón, María del Mar (2023)
Nowadays victimizations against the LGTBIQ+ community in Europe and more specifically in Spain have increased their numbers worryingly. Public Authorities play a key role in the prevention and struggling areas. In the same sense, they should guarantee this vulnerable group to be able to exercise their right of access to justice without barriers. Nevertheless, the statistics point out an important dark figure, being the distrust in criminal control institutions the main reason for the LGTBIQ+ community not reporting the facts related to their orientation, and/or sexualgender identity. This paper aims to offer a general overview of this issue in Spain and a review of the main public politics and some examples of good practices in the third sector entities that protect the right of access to justice for this community, strengthening and reforming institutions so they become friendly, confident, and safe places.